Dynamic Response of the Thoracolumbar and Sacral Spine to Simulated Underbody Blast Loading in Whole Body Post Mortem Human Subject Tests - Sherman, Donald; Somasundaram, Karthik; Begeman, Paul; Foley, Sierra; Greb, Jason; Bir, Cynthia; Demetropoulos, Constantine K.; Cavanaugh, John M. (Annals of biomedical engineering, 2021)
Fourteen simulated underbody blast impact sled tests were performed using a horizontal deceleration sled with the aim of evaluating the dynamic response of the spine in under various conditions. Conditions were characterized by input (peak velocity and time-to-peak velocity for the seat and floor), seat type (rigid or padded) and the presence of personnel protective equipment (PPE). A 50% (T12) and 30% (T8) reduction in the thoracic spine response for the specimens outfitted with PPE was observed. Longer duration seat pulses (55 ms) resulted in a 68–78% reduction in the magnitude of spine responses and a reduction in the injuries at the pelvis, thoracic and lumbar regions when compared to shorter seat pulses (10 ms). The trend analysis for the peak Z (caudal to cranial) acceleration measured along the spine showed a quadratic fit ( p < 0.05), rejecting the hypothesis that the magnitude of the acceleration would decrease linearly as the load traveled caudal to cranial through the spine during an Underbody Blast (UBB) event. A UBB event occurs when an explosion beneath a vehicle propels the vehicle and its occupants vertically. Further analysis revealed a relationship ( p < 0.01) between peak sacrum acceleration and peak spine accelerations measured at all levels. This study provides an initial analysis of the relationship between input conditions and spine response in a simulated underbody blast environment.